VD_FINDINFO HC / 2016 / 95 vom 21. Januar 2016 - VD Tribunal cantonal (2016)
BAIL À LOYER, RÉSILIATION, COMMUNAUTÉ HÉRÉDITAIRE, COLOCATAIRE, LÉGITIMATION ACTIVE ET PASSIVE, HÉRITIER, BAIL COMMUN, CONSORITÉ | 560 CC, 602 CC, 266i CO